Transcription-independent expression of PKMζ in the anterior cingulate cortex contributes to chronically maintained neuropathic pain. Issue 1 (June 2018) - Ko, Hyoung-Gon; Ye, Sanghyun; Han, Dae-Hee; Park, Pojeong; Lim, Chae-Seok; Lee, Kyungmin; Zhuo, Min; Kaang, Bong-Kiun
Protein kinase M ζ is well known for its role in maintaining memory and pain. Previously, we revealed that the activation of protein kinase M ζ in the anterior cingulate cortex plays a role in sustaining neuropathic pain. However, the mechanism by which protein kinase M ζ is expressed in the anterior cingulate cortex by peripheral nerve injury, and whether blocking of protein kinase M ζ using its inhibitor, zeta inhibitory peptide, produces analgesic effects in neuropathic pain maintained chronically after injury, have not previously been resolved. In this study, we show that protein kinase M ζ expression in the anterior cingulate cortex is enhanced by peripheral nerve injury in a transcription-independent manner. We also reveal that the inhibition of protein kinase M ζ through zeta inhibitory peptide treatment is enough to reduce mechanical allodynia responses in mice with one-month-old nerve injuries. However, the zeta inhibitory peptide treatment was only effective for a limited time.